ANALISIS APLIKASI STRUKTUR TRUSS BERPENAMPANG MELINTANG SEGITIGA UNTUK JEMBATAN JALAN RAYA - Zainuddin Zainuddin; T. Budi Aulia; Cut Ranian (Jurnal Teknik Sipil Unaya, 2015)
Truss structure which is often used for primary girder  of bridge of highway is a Warren or Pratt  type, what is its use combined with two horizontal truss attached below and above functioning as truss of wind bracing. Though have space dimension, but its structure is not pure of truss space, practically its analysis is done to each truss, vertical and horizontal which is considered as plane truss.  Truss structure with a trianggular  cross section type represent other alternative from structure truss which can is also used as a highway bridge structure, and this type truss represent purification truss space. Beside that, structurally entire element truss together have the contribution to arrest forced from all direction, and cause this type truss is more stable in arrest torsion and shear compared to a other structure truss bridge type. Method used to analyse structure of truss that is stiffness matrix method by means of  assist calculation of Microsoft Excel 2007. Result to be reached from this analysis is to find relation of between span length, depth of truss and to the number of panel, to weight of structure and translation of a joint; utilize to get optimum weight and translation of joint. Pursuant to result analyse to three group of sample truss model, each group consisted of three sample, in each depth condition of certain truss, there's only one optimum weight value at one particular truss, and angle of inclination of diagonal and also the span-depth ratio and depth of  economic truss still stay in gyration of economic values is such as those which applied for plane truss